Peculiarities of the principles of criminal and administrative law during the provision of the right to education in the conditions of the introduction of martial law: legal regulation and international standards - Chorna, Alina; Leheza, Yevhen; Merdova, Olha; Vlasenko, Denys; Davlatov, Shavkat (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The purpose of the research is to consider the essence of principles of criminal law and the particularities of their implementation under conditions of war. It has been substantiated that the main idea of criminal law principles consists of their systematic, balanced, comprehensive performance in relation to subjects of criminal legal concerns. The mentioned principles apply to law-making and law enforcement, both in peacetime and wartime. The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method, and methods of analysis and synthesis. A conclusion has been made about the necessity to observe human rights standards in prosecuting persons who have committed crimes against humanity and have been involved in such crimes. The civilized world must meet civilized standards and ensure security through civilized means.